2013
DOI: 10.1177/0141076813486261
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines in cardiac clinical practice: evaluation of their methodological quality using the AGREE II instrument

Abstract: SummaryAlthough clinical guidelines have an influential role in healthcare practice, their development process and the evidence they cite has been subject to criticism. This study evaluates the quality of guidelines in cardiac clinical practice by examining how they adhere to validated methodological standards in guideline development. A structured review of cardiac clinical practice guidelines published in seven cardiovascular journals between January 2001 and May 2011 was performed. The AGREE II assessment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
2
28
0
4
Order By: Relevance
“…First, the comprehensive size of each guideline meant that they were more descriptive in their methods than those that are published in peer-reviewed journals and also have been subjected to quality assessment [24]. Second, it was clear to the assessors that these guidelines had a predefined structure that reflected key aspects of the developmental rigor domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the comprehensive size of each guideline meant that they were more descriptive in their methods than those that are published in peer-reviewed journals and also have been subjected to quality assessment [24]. Second, it was clear to the assessors that these guidelines had a predefined structure that reflected key aspects of the developmental rigor domain.…”
Section: Discussionmentioning
confidence: 99%
“…These are whether facilitators and barriers to implementation are described, if advice or tools to aid implementation are provided, consideration of potential resource implications of applying the guideline, and the presentation of a monitoring or auditing criteria. Studies of guideline quality that use AGREE II commonly cite this deficiency, which implies guideline developers throughout medicine ignore its importance [24,25]. Guidelines that fail to address these areas may be vulnerable to poor uptake by healthcare professionals and therefore have a limited effect on improving healthcare quality [9].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of guidelines showed that they were high in quality for scope and purpose, stakeholder involvement, rigor of development and clarity of presentation, but consistently lacking in applicability. [10][11][12][13][14] This refers to guideline implementation tools (GItools) such as training material (e.g., workshop slides, self-directed learning kits), guideline summaries or algorithms, patient information, or guidance for evaluation (e.g., quality indicators, audit instructions). Focus groups found that health professionals were frustrated and uncertain about how to implement guidelines.…”
mentioning
confidence: 99%
“…Low scoring was most consistently reported for the following domains: stakeholder involvement (specifically very restricted patient participation and involvement in the guideline development)[44,48,50], rigor of development (guidelines were mostly based on expert opinion rather than evidence) [41,44,49], applicability [41,43,44,46,48-51], editorial independence [41,44,49]. These findings are comparable to those we obtained while assessing the CPGs on vitamin D replacement in patients undergoing bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%